Measuring the Technological Innovativeness in PT Dirgantara Indonesia, Case: The Development of Aircraft N219 - Saraswati, Annisa Putri; Aldianto, Leo (Journal of Business and Management, 2014)
Many management experts who claim that innovation is one of the guarantees for the company or organization in improving its competitiveness. But how to respond to and anticipate the pace through innovation is not simple and easy to do. In the word Economic Forum, there are many companies in Indonesia which is seen as less innovative, although Indonesia was ranked 38th in general and ranking 33 of 148 countries in the innovation pillar. Since 2006, PT Dirgantara Indonesia aircraft N219 develop capacity of 19 people to replace existing aircraft pioneer. Indonesian manufacturing companies need to improve their innovation and thus they require some measurement framework to help them achieve it. As background the importance of innovation for companies in Indonesia, researchers provide a theoretical review of measurement innovation activities based on technological innovation and management innovation itself. This final project is to identify activities of innovation and management of innovation at PT Dirgantara Indonesia for the development of aircraft N219. Measurement of innovation categorized into CLAS-Category (Category Creative, Lucky Category, Automatic Category and Superb Category). In collecting the data, the sample used is 50 people by distributing questionnaires to employees and interview people in the top management ranks in PT Dirgantara Indonesia. The results of this study are PT Dirgantara Indonesia has conducted several activities have supported innovation and management innovation for the development of several aircraft N219, but it still needs to be improved and enhanced return. In the measurement of innovation, PT Dirgantara Indonesia fall into the superb category of innovation though not yet reached the highest point. That is, PT Dirgantara Indonesia is a company that enjoys and benefits from the employee's ability to perform the required activities of the company during the process of innovation and good for the environment as well as the impact of the innovation practices of good management in the areas of strategy, resources, and operations.Keywords: The activities of innovation, The management of innovation, and Innovation measurement.